DEVELOPING AN EMERGENCY-CONSERVATION PROGRAM FOR THE CULTURAL HERITAGE OF ABU DHABI, UNITED ARAB EMIRATES - Aqeel, Aqeel Ahmed; Chabbi, Amel; Mahdy, Hossam; Malekabbasi, Ali; Marcus, Benjamin; Ali, Salman Muhammad (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Over-shadowed by its rapid growth and new developments, the historic environment of Abu Dhabi is, in fact, rich in cultural heritage that dates back to the 3rd millennium BCE and is comprised of cultural landscapes, archaeological sites, and vernacular buildings built with traditional materials, such as earth or stone. The fragile condition of these buildings and archaeological sites has made immediate action imperative. The Abu Dhabi Authority for Culture and Heritage launched the irst comprehensive program for Emergency Conservation in 2009. The program, intended as a “irst response,” addresses the urgent conservation needs of these structures by ensuring their safety and stability until further measures can be planned. The program was irst developed on a building-based approach; however, it was dificult to prioritize interventions and only six buildings were stabilized in 2009. To better prioritize across multiple buildings and sites, a taskbased approach was adopted. A system for rapid assessment, prioritizing and planning intervention tasks, and implementation and reporting was developed (Ziegert, 2010). For each task, the material resources and time needed were estimated. Tasks were then rated, organized and scheduled based on a set of priorities into six-month cycles. The progress of a task was tracked and documented with standardized forms. The Emergency Conservation Program has thus far been very successful in rapidly tackling a large number of issues among numerous buildings and sites, and ensuring that they are stable before carrying out longer-term conservation. 85% of emergency issues have been addressed since the program’s inception with over 36 sites in stable condition. This paper will present the methodology developed for this program and demonstrate how it can be applied in response to emergency situations, such as natural disasters.